Implementasi Peraturan Wali Kota Bandung Nomor 004 Tahun 2019 tentang Kurikulum Pendidikan Karakter dalam Meningkatkan Mutu Lulusan - Sya'bi Arifin Rifa'i; Astuti Darmiyanti (Journal on Education, 2023)
The purpose of this study was to find out how the implementation of the teacher's code of ethics in the MDA Raudlatul Athfalis Sa'adah Karawang learning environment, and to find out what implementation model was carried out. The research method used is field research with a qualitative descriptive approach as well as observation and interview methods. The results of this study are, the implementation of the teacher's code of ethics carried out by teachers in the MDA Raudlatul Athfalis Sa'adah Karawang learning environment is that every teacher at MDA Raudlatul Athfalis Sa'adah Karawang has an exemplary attitude, empathy, always gives appreciation, attention , and open. Then the implementation model carried out by teachers in the MDA Raudlatul Athfalis Sa'adah Karawang learning environment is by example and habituation. This implementation was successfully carried out by teachers in the MDA Raudlatul Athfalis Sa'adah learning environment due to the cohesiveness of each teacher, good communication with student guardians, and monitoring from the school principal.